Investigating entrepreneurial opportunities a practical guide for due diligence - Green, Richard P.; Carroll, James J.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 2000)
Both authors have bought and sold several businesses, and here they explain the process in simple, easy-to-follow steps that cover all the basics such as market, products, insurance facilities, assets and short and long term liabilities.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Entrepreneurship; Electronic books